Strategic Dynamics and the Implications of Identity Politics in the 2024 General and Local Elections in Papua - Farid Al Hadana; Ratnaningrum Zusyana Dewi; Sakhidad Mahdiyar (Universitas Tribhuwana Tungga Dewi, 2026)
The 2024 General and Regional Elections in Papua serve as a critical focal point for understanding the evolving role of identity within Indonesia’s democratic contestation. This research seeks to decode the mechanisms through which political actors manufacture and institutionalize identity claims, while evaluating their subsequent effects on social cohesion and deliberative discourse. Adopting a qualitative-interpretive lens and an embedded comparative case study design, the study processes data from official records, political rhetoric, and social media via hybrid coding, discourse analysis, and process tracing. The results reveal a strategic shift: identity has moved beyond a quest for recognition to become a calculated electoral instrument that reinforces